2020
DOI: 10.1007/s10853-020-04942-7
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and optimization of biomimetic materials simulating solar spectrum reflection characteristics of natural leaves

Abstract: Solar spectrum reflection characteristics of natural leaves are caused by the absorption and scattering processes of incident radiation in the leaves. To realize hyperspectral camouflage in the background of vegetation, two types of biomimetic materials are prepared. One type utilizes Cr 2 O 3 particles to simultaneously simulate the absorption characteristics in the visible light band and the scattering characteristics in the solar spectrum band and is named as COG-BM. The other type contains chlorophyll and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The micro uidic textiles was demonstrated for ground hyperspectral camou age in the solar radiation spectrum in 300-2500 nm 34 . As a common ground vegetation with complex optical characteristics 35 , natural leaves were taken as the background (Supplementary Note 3).…”
Section: Resultsmentioning
confidence: 99%
“…The micro uidic textiles was demonstrated for ground hyperspectral camou age in the solar radiation spectrum in 300-2500 nm 34 . As a common ground vegetation with complex optical characteristics 35 , natural leaves were taken as the background (Supplementary Note 3).…”
Section: Resultsmentioning
confidence: 99%
“…[20][21][22] This makes Cr 2 O 3 a proper pigment to simulating the solar spectrum reflection characteristic of green leaf for camouflage purpose. 23 Since Cr 2 O 3 coatings exhibits high reflectance in whole near infrared (NIR) region that carry 51% of solar energy, it has the potential to be utilized as coloured radiative coolers which can reduce solar heating and improve appearance simutaneously. 24,25 Applying the inkjet printing technology with Cr 2 O 3 being the pigments can significantly simplify the process from designing to coating a new camouflage pattern and reduce the cost.…”
Section: Introductionmentioning
confidence: 99%
“… 20–22 This makes Cr 2 O 3 a proper pigment for simulating the solar spectrum reflection characteristic of green leaves for camouflage purpose. 23 Since Cr 2 O 3 coatings exhibit high reflectance in the whole near-infrared (NIR) region that carry 51% of solar energy, it has the potential to be utilized as coloured radiative coolers, which can reduce solar heating and improve appearance simultaneously. 24,25 …”
Section: Introductionmentioning
confidence: 99%
“…The solar spectral reflectance characteristics of natural leaves have been widely reported in previous literature [ 1 , 3 ]. The solar spectral reflectance of three different green leaves is shown in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, for composite coating, Gao et al [ 11 ] prepared a biomimetic material comprising of a hygroscopic material and Cr 2 O 3 to counter the hyperspectral detection through the simulation of the solar spectral reflection of a natural leaf. Furthermore, Xu et al [ 3 ] reported two types of biomimetic materials, whereby one utilized Cr 2 O 3 particles, while the other contained chlorophyll and TiO 2 particles. The results showed that both biomimetic materials were able to emulate the solar spectral reflectance characteristics exhibited by the leaf.…”
Section: Introductionmentioning
confidence: 99%